2020
DOI: 10.1155/2020/3503165
|View full text |Cite
|
Sign up to set email alerts
|

Protective Effect of Coconut Oil Meal Phenolic Antioxidants against Macromolecular Damage: In Vitro and In Vivo Study

Abstract: Coconut oil meal, a cheap by-product of coconut oil production, is a rich source of phenolic antioxidants. Many age-related diseases are caused by reactive oxygen species- (ROS-) induced damage to macromolecules such as lipids, proteins, and DNA. In the present study, the protective effect of the phenolic extract of coconut oil meal (CMPE) against macromolecular oxidative damage was evaluated using in vitro and in vivo models. Sunflower oil, bovine serum albumin (BSA), and plasmid DNA were used in the in vitro… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
6
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
7
1

Relationship

3
5

Authors

Journals

citations
Cited by 9 publications
(7 citation statements)
references
References 33 publications
1
6
0
Order By: Relevance
“…The phenolic contents in coconut kernel components (white coconut meat and testa) are not fully incorporated into coconut oil during wet or dry extraction methods. Therefore, the residue after the expulsion of coconut oil from coconut kernel components is also rich in phenolic antioxidants (Illam et al, 2017;Karunasiri et al, 2020b).…”
Section: Coconut Testamentioning
confidence: 99%
“…The phenolic contents in coconut kernel components (white coconut meat and testa) are not fully incorporated into coconut oil during wet or dry extraction methods. Therefore, the residue after the expulsion of coconut oil from coconut kernel components is also rich in phenolic antioxidants (Illam et al, 2017;Karunasiri et al, 2020b).…”
Section: Coconut Testamentioning
confidence: 99%
“…A main undesirable effect of ROS is presented on cellular macromolecules, such as lipids and proteinlipid that can lead to cell membrane oxidative damages [70,71]. We found that A. citriodora extract can reduce lipid peroxidation and ethanol-induced protein oxidation.…”
Section: Discussionmentioning
confidence: 72%
“…Consumption of antioxidant‐rich foods increases the serum antioxidant capacity in humans as indicated by Trolox equivalent antioxidant capacity and ferric reducing power (Cao et al., 1998; Talegawkar et al., 2009)]. Treatment of HepG2 cells with phenolic antioxidants increases GSH/GSSG ratio and inhibits the oxidative stress‐induced macromolecular damage (Karunasiri et al., 2020). Strong correlation between serum chlorogenic acid content and serum antioxidant capacity in response to intervention in combination with edible oils observed in the present study suggests that edible oils may support reduced oxidative damage of macromolecules due to improved absorption of antioxidants.…”
Section: Discussionmentioning
confidence: 99%
“…GSH/GSSG ratio was determined using GSH/GSSG‐Glo™ Assay kit (Promega) (Karunasiri et al., 2020). Plasma sample (25 µl) and Lysis Reagent (12.5 µl) were mixed by pipetting, and the mixture was incubated at RT for 5 min.…”
Section: Methodsmentioning
confidence: 99%